Kualitas Pelayanan Publik Dalam Meningkatkan Kepuasan Masyarakat Pada Kantor Camat Abang Kabupaten Karangasem - Ratna Juwita, Ni Made (CITIZEN CHARTER, 2017)
The sub-district office of Abang is one of the working units of the district of Karangasem. The purpose of the office is to improve the coordination of government administration, public service, and empowerment of village communities in the sub-district of Abang. The office often experience problems related to the quality of service, therefore a research is needed tp know why the services are not optimal. In this study the researcher used descriptive qualitative research method, where the data collected by doping the observation and interview and linked with existing concept theory. The researcher used a theory which focuses on the quality of service stated by Parasuraman, where according to him, in order to know the service quality that is perceived significantly by costumer, the are some indicator measurements of costumer satisfaction which isi n five dimensional of service quality namely physical proof, reliability, perception, assurance and empathy. Those indicators are associated with the service of the sub-district office to the community in the territory of Abang. After the implementation of such research, it can be concluded that the quality of public services in the office is inadequate service facilities with the number of customers every day. This can be seen from the table which is not available for writing in the waiting room, information facilities that are not yet available, facilities such as generators which are less optimized and provision of internet access that is not yet available. Keywords: Public Services, Customer Satisfaction, The Sub-district of Abang